ANALISIS INTELLECTUAL CAPITAL DENGAN IB-VAIC TERHADAP RETURN ON ASSET (STUDI EMPIRIS PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2011-2014) - DINA KAMILIA, NUR (Jurnal Akuntansi AKUNESA, 2016)
This research to determine and obtain empirical evidence about the effect of Intellectual Capital by using iB-VAICTM on Return On Asset (ROA) Islamic Banks. This research is quantitative research and used secondary data from form financial statements of Islamic bank for 2011-2014 period. The sampling technique used purposive sampling which obtained 10 Islamic Banks and the data used as many as 40 data. The independent variables in this research is Intellectual Capital (IC) and the dependent variable is Return on Assets (ROA). The research have to test the classical assumption that including normality test, autocorrelation, and heteroscedasticity. The analysis used a simple linear regression analysis. The results showed that a significant variable between intellectual capital of Return On Asset (ROA). This is evidenced by the results obtained calculation t test with a significance value (p) is smaller than the level sigfikansi 0.05 (0.000 < 0.05). the calculation of iB-VAIC and ROA showed that iB-VAIC increased the ROA also increased.